Preliminary Phytochemical Analysis, Antimicrobial Activity of Nycthanthes Arbor-Tristis Linn Flowers (Stalk) - Sandeep, Tadikonda; Hymavathi, Valluru; Likhitha Krishna Priya, Tadiboyina; venkata sai prasanna, Seggam Naga; Anusha, Pilli; Meghana, Karumanchi; Raheela Sulthana, Mohammed; Jyothsna, Mudigarla (Journal of Neonatal Surgery, 2025)
Phytochemical Evaluation and Antibacterial Activity of Nyctanthes arbortristis L. Stalk Extracts. Nyctanthes arbortristis L., commonly known as the night-flowering jasmine, is recognized for its medicinal properties. Previous studies have reported the antioxidant activities of the plant, but antimicrobial activities, particularly in its flowers and stalks, remain underexplored. This study focuses on the extraction, phytochemical analysis, and antimicrobial evaluation of the hydroalcoholic extract and its successive fractions from the stalk of Nyctanthes arbortristis L. The hydroalcoholic extract of Nyctanthes arbortristis stalk was subjected to successive extraction and phytochemical analysis, which included screening for alkaloids, glycosides, flavonoids, and steroids. Chromatographic separation was employed to isolate the fractions, and antibacterial activity was evaluated against gram-positive and gram-negative bacterial strains using standard microbiological methods. Phytochemical analysis revealed the presence of alkaloids, glycosides, flavonoids, and steroids across all extracts. The chromatographic fractions displayed variability in their compound profiles. The hydroalcoholic extract did not show significant antibacterial activity, while the successive fractions exhibited marked inhibitory effects against both gram-positive and gram-negative bacteria. The fractions, which contained higher concentrations of bioactive metabolites, demonstrated enhanced antibacterial properties compared to the hydroalcoholic extract.